Correlation between Blood Pressure Responses to Dietary Sodium and Potassium Intervention in a Chinese Population - Zhao, Qi (2009)
BACKGROUND: Blood pressure (BP) responses to dietary sodium and potassium intake vary among individuals. We examined the correlation between BP responses to dietary low-sodium, high-sodium, and potassium supplementation interventions in a feeding study. METHODS: 1,906 Chinese aged ≥16 years participated in the dietary intervention which included a 7-day low-salt intervention (51.3 mmol/day), a 7-day high-salt intervention (307.8 mmol/day), and a 7-day high-salt plus potassium supplementation (60 mmol/day) intervention. BP was measured 9 times during the 3-day baseline observation and during the last 3 days of each intervention phase using a random-zero sphygmomanometer. RESULTS: The correlation coefficients (95% confidence intervals [CI]) of the BP responses to low-sodium and high-sodium intervention were −0.47 (−0.51 to −0.44), −0.47 (−0.50 to −0.43), and −0.45 (−0.49 to −0.42) for systolic, diastolic, and mean arterial pressure (MAP), respectively (all p<0.0001). The correlation coefficients (95% CI) of the BP responses to high-sodium intervention and potassium supplementation were −0.52 (−0.56 to −0.49), −0.48 (−0.52 to 0.45), and −0.52 (−0.55 to −0.48) for systolic, diastolic, and MAP, respectively (all p <0.0001). The kappa coefficients were moderate, varying from 0.28 to 0.34, between BP responses to low-sodium and high-sodium intervention (all p <0.0001). CONCLUSIONS: These results indicate there is a moderate correlation between BP responses to low-sodium and to high-sodium interventions, and BP responses to high-sodium intervention and potassium supplementation. Furthermore, our study suggests that individuals who were more sensitive to high-sodium diet might benefit more from a low-sodium and/or high-potassium intervention aimed at lowering BP levels.